OPTIMIZING THE USE OF ULOLANANG KECUBUNG NATURAL RESERVE AS LEARNING SOURCES OF BIODIVERSITY - Nugroho, Ary Susatyo (BIOMA, 2013)
The learning processof biodiversity insome schoolsit is lessoptimal, especially in theuse of learning sources. The natural reserveis anatural environments potential as a sources oflearning. The natural reserveUlolanangKecubunghasa highbiodiversity, including diversity of ecosystems, species andgenetic. Ecosystemdiversity includesnatural ecosystems, semi-naturalecosystemsandartificial ecosystems. Species diversity includes various types of vegetation such as trees, shrubs, epiphytes, lianas, ferns, and various types of animals such as long-tailed monkeys, butterflies, birds, and so forth. In addition to high biodiversity, nature reservation Ulolanang Kecubung very easy reach so it is ideal for use as a learning sources.Keywords:natural reserve, biodiversity, learning sources